Analysis of rocket fuels and problems of their application on the example of Ukraine - Trofimov, Igor; Boichenko, Sergii; Shamanskyi, Sergii (Technology audit and production reserves, 2020)
The object of research is the problems of rocket fuel application, the state of art and prospects. These problems are characteristic of almost the entire range of brands of modern rocket fuels suitable for application. These are problems with the basic physic-chemical and operational properties, technical requirements for the quality of rocket fuel, problems with the functioning of the refueling infrastructure, as well as ensuring the purity of rocket fuels. Given the ban on the use of highly toxic poisonous rocket fuels based on nitric acid, there is a problem of replacing them with less toxic. This problem is aggravated by the lack of production of their own petroleum-based hydrocarbon rocket fuels in many countries. In general, it leads to acute problems with the supplying spacecraft and rocket carriers with rocket fuels. In particular, such a problem arises in Ukraine with Ukrainian-made missiles. The constant attention to the problem of the aviation and rocket fuels quality results from many factors. The research has used a comprehensive approach to fuel quality assessment, analysis of world experience, synthesis of results and retrospectives, historical-evolutionary and logical approach. High level of fuels purity provides high reliability, safety of flights, increases technical resource of engine units. Therefore, expenses for achievement and maintenance of necessary level of purity of fuel and working liquids are quite justified. The result of the research is a classification of liquid rocket fuels based on their component composition and chemical structure. Requirements to energy, kinetic, operational characteristics, ecological and economic properties of liquid rocket fuels (LRF) are formulated. Given the unsatisfactory environmental conditions, the use of kerosene as a rocket fuel is more relevant compared to heptyl rocket fuel. Jet fuels T-1, T-6, T-8B are well suited for space technology of many countries, but very few countries can produce them. Purchasing in neighboring countries is not always possible for a number of reasons. Comparative analysis shows that liquid rocket fuel RP-1 in most respects is an analogue of jet fuel T-1 and T-6 and can be used as a substitute for rocket carriers. However, the problem of development of standards and regulations on quality control of LRF during their storage and operation is not solved. In particular, there is no clear regulation for the process of refueling LRF missiles at low temperatures. There are no regulations on the content of free and dissolved water and mechanical impurities in the LRF, unlike aviation fuels. One of the promising types of rocket fuels are hydrogen fuel cells. The results of the research can be applied in the field of spacecraft operation, as well as refueling infrastructure and cleanliness of rocket fuels. The research results can also be used by chemical experts, specialists in the field of operation of refueling and storage of LRF.